Islamization of knowledge : a comparative study of al-Atlas and al-Faruqi - Khan, Abdul Basir Aziz (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1998)
This study compares the two approaches to Islamization of knowledge pioneered by Syed Naquib al-Attas and Ismail Raji al-Faruqi. It discusses some of the key concepts used by the two scholars and compares the definitions, guidelines and methods of Islamization of knowledge. Finally, it examines the two scholars' understanding of the causes of the crisis in Muslim education and methodology of knowledge. Using the comparative method, the study found that there are notable similarities between the two approaches as far as the general understanding of Islamization of knowledge is concerned. Both agree that the dissemination of secularism in the Muslim world has created dualism in education. However, their views diverge on the guidelines and methods of Islamizing knowledge. Al-Attas contends that isolating the Western concepts and replacing them with Islamic concepts can Islamize knowledge. Al-Faruqi, on the other hand, argues that Islamization of knowledge must aim at integrating the two systems into one so that both systems benefit from each other.